Feasibility of a truncated surveillance schedule for patients following curative intent treatment for carcinoma of the oral cavity. Issue 8 (August 2022) - Manikantan, K.; Jain, P.V.; Sharan, R.; Arun, P.
Abstract: The purpose of this study was to determine whether a regular follow-up schedule with examination by clinicians results in a better detection rate of disease recurrence and eventual better clinical outcomes when compared to patients who present with symptoms to the clinic and are subsequently detected to have a recurrence of oral squamous cell carcinoma. Retrospective data from 642 patients who underwent treatment for oral squamous cell carcinoma at a tertiary level cancer centre were analysed. Of the 642 patients, 197 had recurrences of which 108 were detected on regular follow-up and 87 were detected in patients presenting out of schedule with symptoms; two patients were detected to have recurrence at another centre, but their mode of detection could not be ascertained. There was no difference in the loco-regional recurrence-free survival or disease-free survival between the two groups. A strict follow-up schedule in the first year followed by a more flexible symptom-based schedule in the subsequent years, with supplementation of imaging if clinically indicated, should be an adequate surveillance plan for oral cancer patients.